First records of Stigmatogobius yanamensis Visweswara Rao, 1971 (Perciformes: Gobiidae) in Indonesian waters - IQBAL, MUHAMMAD; SETIAWAN, ARUM; YUSTIAN, INDRA (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2024)
Stigmatogobius yanamensis is a small and cryptic goby, whose distribution remains poorly known. On 2 April 2016, two specimens of S. yanamensis with a standard length of 20-21 mm were caught by hand net in the intertidal zone of estuarine mangroves, above a muddy substrate at the mouth of Sembilang River, South Sumatra Province, Indonesia. In addition, ten specimens were collected on 1-4 June 2023 in Sungsang (c. 40 km from Sembilang River) South Sumatra Province, Indonesia. This finding constitutes the first records of S. minima in Indonesian waters